Seasonal Effect On Blood Biochemical Parameters In Kankrej Cattle At Different Level Of Their Productivity - Das, Hemen; Lateef, A.; Panchasara, H.H.; Sanap, M.J.; Nilufar, H.; Parsani, H.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present study was carried out to evaluate the effect of seasons on vital biochemical parameters of Kankrej cattle at different level of their milk yielding ability. Blood samples were collected in all three seasons of the year viz. winter, summer and monsoon from the three experimental groups i.e. group-I (low yielder), group II (medium yielder) and group III (high yielder). There was non significant variation in glucose level amongst the groups except it was significantly higher in group III during monsoon. Similarly, significantly higher values of total protein were recorded in group III and group II during summer. Conversely, BUN level did not vary significantly amongst the groups throughout the year. However, there was non-significant but progressive increase in calcium level from winter to monsoon. The seasonal trend in phosphorus level was fairly definite and variations between seasons and groups were significant. The magnesium level decreased non-significantly from monsoon to summer.
Keywords: Kankrej; Season; Milk yield; Biochemical; Lactation